2017
DOI: 10.1080/13543784.2018.1417383
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for the treatment of alcohol use disorder

Abstract: Alcohol misuse is the fifth leading risk factor for premature death and disability worldwide. Fewer than 10% of afflicted Americans receive pharmacological treatment for alcohol use disorder. Gabapentin is a calcium channel GABAergic modulator that is widely used for pain. Studies showing reduced drinking and decreased craving and alcohol-related disturbances in sleep and affect in the months following alcohol cessation suggest therapeutic potential for alcohol use disorder. Areas covered: Human laboratory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 97 publications
1
75
0
12
Order By: Relevance
“…Because of the structural similarities between gabapentinoids and GABA, and the known influence of the M-current in many of the disease states responsive to gabapentinoids (epilepsy, pain, anxiety, alcohol withdrawal) (Blackburn-Munro et al, 2005; Kang et al, 2017;Mason et al, 2018), we hypothesized that gabapentinoids might modulate KCNQ2/3 channels. Here, using This article has not been copyedited and formatted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the structural similarities between gabapentinoids and GABA, and the known influence of the M-current in many of the disease states responsive to gabapentinoids (epilepsy, pain, anxiety, alcohol withdrawal) (Blackburn-Munro et al, 2005; Kang et al, 2017;Mason et al, 2018), we hypothesized that gabapentinoids might modulate KCNQ2/3 channels. Here, using This article has not been copyedited and formatted.…”
Section: Introductionmentioning
confidence: 99%
“…We found that, like the anticonvulsant retigabine (Kim et al, 2015;Schenzer et al, 2005), GABA binds to a conserved tryptophan (W265) on KCNQ3 to activate KCNQ3 homomers and KCNQ2/3 heteromers (Manville et al, 2018) (Fig. 1B-D).Because of the structural similarities between gabapentinoids and GABA, and the known influence of the M-current in many of the disease states responsive to gabapentinoids (epilepsy, pain, anxiety, alcohol withdrawal) (Blackburn-Munro et al, 2005; Kang et al, 2017;Mason et al, 2018), we hypothesized that gabapentinoids might modulate KCNQ2/3 channels. Here, using This article has not been copyedited and formatted.…”
mentioning
confidence: 99%
“…• It reduces the release of glutamate, a key component of the excitatory system 16 • It increases the concentration of gammaaminobutyric acid (GABA), the main inhibitory neurotransmitter in the brain 7 • By binding the alpha-2-delta type 1 subunit of voltage-sensitive calcium channels, 8,[15][16][17] it inhibits excitatory synapse formation independent of calcium channel activity 16 • By blocking excitatory neurotransmission, it also may indirectly increase the concentration of GABA in the central nervous system 16,17 • It modulates action of glutamic acid decarboxylase (involved in the synthesis of GABA) and glutamate synthesizing enzyme to increase GABA and decrease glutamate. 17…”
Section: ■ Gabapentin Reduces Excitationmentioning
confidence: 99%
“…18 Alpha-2-delta type 1 subunits of calcium channels are upregulated in the reward centers of the brain by addictive substances, including alcohol. 16 Alcohol interacts with corticotropin-releasing factor and several neurotransmitters, 18 and specifi cally affects neuropathways involving norepinephrine, GABA, and glutamate. 19 Alcohol has reinforcing effects mediated by the release of dopamine in the nucleus accumbens.…”
Section: Modesto-lowe and Colleagues ■ Alcohol's Actionsmentioning
confidence: 99%
See 1 more Smart Citation